Answer:0.0057
Step-by-step explanation:
(1,-1)(2,2)
slope = (2 - (-1) / (2 - 1) = 3/1 = 3
y = mx + b
slope(m) = 3
use either of ur points...(2,2)...x = 2 and y = 2
now we sub and find b, the y int
2 = 3(2) + b
2 = 6 + b
2 - 6 = b
-4 = b
so ur equation is : y = 3x - 4
Answer:
x=11
Step-by-step explanation:
The switch case works like an if or if-else, where each of the cases are conditionals. Here we have 7 cases and we know that our variable begins with x=5.
First, it enters to case 5 because of x=5, so x+=3, this means we add 3 to the actual value of the variable ⇒ x=8.
At this point, if there's not break the program continues to the next case, executing the statements until a break or the end on the switch is reached.
In this order, the x = 8 and next we add 1 (case 6) ⇒ x=9. We add 2 (case 7) x+=2 ⇒ x=10. Then we rest 1 (case 8) ⇒ x=9 and then we add 1 again as in case 9 ⇒ x=11.
Answer:
A.7
5x7=35x7=245 and so on
Step-by-step explanation:
The correct answer is S =7